Peningkatan Taman Doa dengan Pendekatan Kolaboratif untuk Ruang Spiritual yang Inspiratif di Gereja Santo Leo Agung, Jakarta: Enhancement of A Prayer Garden through a Collaborative Approach for An Inspiring Spiritual Space at St. Leo Agung Church, Jakarta - Prabawasari, Veronika Widi; Furuhitho, X.; Susanto, Remigius Hari; Nugroho, Agus; Christina, Erma Triawati; Gunarto, Thomas Yuni (Sam Ratulangi University, 2025)
This Community Service (PkM) activity aims to address the needs of the congregation of St. Leo Agung Parish, East Jakarta, in enhancing and realizing a sacred and tranquil prayer garden as a means of devotion to Mary, Mother of the Redeemer. Stemming from the church's existing but unrealized master plan, this project faced the primary challenges of a limited land area of 67.20 m², coupled with the necessity to preserve existing trees. Through a collaborative approach, this PkM activity focused on two core areas: prayer garden planning and construction management. In the planning phase, the PkM team developed a prayer garden design embodying the concept of